Influence of Degradation of PLA with High Degree of Crystallinity on Fungal Community Structure in Compost. Issue 3 (1st October 2020) - Karamanlioglu, Mehlika; Alkan, Ümit
Abstract: Degradation rate of poly(lactic acid) (PLA), a compostable plastic, is affected by its physical properties and environmental conditions. Since PLA with different physical properties enter composting systems, investigation of degradation of PLA with strong physical properties in compost at different temperatures and its influence on compost fungal community structure are the main concerns of this study. To determine the effect of slow PLA degradation on fungal communities, PLA granules with high degree of crystallinity, 60%, were incubated in compost at 25 °C and 50 °C for 4 months at 0, 10, 25 and 50% (w/w) concentrations; their degradation rates were compared and impact of PLA degradation on compost fungal communities was examined by terminal restriction fragment length polymorphism (TRFLP). PLA granules in compost at 25 °C showed no physical changes but at 50 °C physical disintegration occurred after 4 months. TRFLP revealed that fungal community profiles in compost were affected by PLA, particularly at 50 °C where PLA degraded. Compost fungal communities in the presence of PLA at 50 °C had more variation, 63%, than at 25 °C (52%). Incubation time affected fungal community structure as during 2nd month, community structure changed specifically at 50 °C and at 50% (w/w) PLA, however, became similar to that in the absence of PLA at the end of 4th month at both temperatures indicating PLA with a high degree of crystallinity causes a temporal perturbation in compost fungal communities. In compost containing PLA at 50 °C, abundance of certain TRFs representing fungal populations increased to 30% which may involve in PLA utilization.